Six Thinkers in Search of the Author - Ekaterina B. Kriukova; Oxana A. Koval (Studia Litterarum)
The article presents a survey of the 20th century intellectual quests related to the problem of the author and her status. The question of authorship becomes a key issue in the modern era for both philosophy and literature. On the one hand, both fields reflect upon the authorship as their own intrinsic principle, on the other hand, both literature and philosophy question the privileged position of the author as the sole meaning-maker. The undertaken comparison of the original interpretations of the prominent 20th century thinkers allows us: (1) to demonstrate how the ideological content of the concept itself has changed, the author being labeled as a co-participant, producer, collective subject, function within discourse, non-reader, and witness; (2) to introduce different strategies of understanding the author’s figure, depending on the chosen point of view; (3) to trace the logic of the transition from the modern to the postmodern through the explication of relations between the author and the character (M. Bakhtin), the author and his work (W. Benjamin), the author and popular culture (T. Adorno), the author and the discourse (M. Foucault), the author and the letter (M. Blanchot), and the author and the Other (G. Agamben).